PENGARUH DISIPLIN DAN KEMAMPUAN KERJA TERHADAP KINERJA PEGAWAI PADA BAGIAN PROTOKOL DAN KOMUNIKASI PIMPINAN KOTA BANDAR LAMPUNG - Ani Heryani; Ade Iskandar; Rizky Destian (e-JKPP, 2021)
The problems faced in the Protocol Section are that there are still some employees who do not understand the assigned tasks, the low responsibility of employees in completing tasks and employee discipline in the Protocol Section is still not effective. The two elements of these variables have an impact on not optimal employee performance. Based on these problems, the problems in this study are: (1) Is there an effect of discipline on employee performance in the Protocol and Communication Section of the Bandar Lampung City Leadership? (2) Is there an effect of work ability on employee performance in the Protocol and Communication Section of the Bandar Lampung City Leadership? (3) Is there any influence of discipline and work ability on employee performance in the Protocol and Communication Section of the Bandar Lampung City Leadership?The purpose of this study was to determine, analyze and explain the effect of discipline and work ability on employee performance in the Protocol and Communication Section of the Bandar Lampung City Leadership, either partially or simultaneously.This study uses descriptive methods and quantitative approaches with product moment analysis tools and multiple linear regression.The results of testing the relationship between discipline and employee performance obtained t count of 9,396. Furthermore, the relationship between work ability and employee performance obtained t count of 5.614. Testing simultaneously or collectively, the calculated F statistical results are 89,419. It is concluded that this study found a significant influence both partially and simultaneously between Discipline and Work Ability on Employee Performance in the Protocol and Communication Section of the Bandar Lampung City Leadership.